2007
DOI: 10.1111/j.1750-3841.2007.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Physiochemical Characteristics of Frankfurters Formulated with Potassium Lactate and Sodium Diacetate before and after Irradiation

Abstract: Quality attributes were evaluated for irradiated (0, 1.8, or 2.6 kGy) frankfurters formulated with 0% or 3% potassium lactate/sodium diacetate solution and stored aerobically or vacuum packaged at 4 degrees C for 4 or 8 wk, respectively. Quality analyses included descriptive sensory panel, pH, L*a*b* color values, and TBARS determination. Aroma and flavor quality were retained for aerobically stored frankfurters with lactate/diacetate throughout shelf-life. Meaty/brothy complex aroma and flavor, smoke aroma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Nanoclay did not have positive effects in decreasing TBARS but it did not have also positive effects on TBARS compared with the control group. The results for the effects of SDA are in agreement with other studies on the effects of SDA on TBARS in sausage (Knight et al., 2007; Sommers & Fan, 2003). The decrease in TBARS in the TBHQ and ST films could be attributed to the antioxidant activity of TBHQ as observed for in vitro antioxidant activity.…”
Section: Resultssupporting
confidence: 91%
“…Nanoclay did not have positive effects in decreasing TBARS but it did not have also positive effects on TBARS compared with the control group. The results for the effects of SDA are in agreement with other studies on the effects of SDA on TBARS in sausage (Knight et al., 2007; Sommers & Fan, 2003). The decrease in TBARS in the TBHQ and ST films could be attributed to the antioxidant activity of TBHQ as observed for in vitro antioxidant activity.…”
Section: Resultssupporting
confidence: 91%
“…Cabeza et al (2009) reported that irradiation of vacuum-packed dry fermented sausages at ≤2 kGy had negligible effects on their sensory characteristics (appearance, odor and taste). The aroma and fl avor quality of irradiated (0, 1.8 or 2.6 kGy) frankfurters formulated with 3% potassium lactate/sodium diacetate solution were retained for 4 weeks under aerobic conditions or for 8 weeks under vacuum packaged conditions at 4 °C (Knight et al, 2007). Hoz et al (2008) suggested that irradiation at 1 and 2 kGy had negligible sensory modifi cations (appearance, odor and fl avor) in irradiated vacuum-packaged dry-cured ham.…”
Section: Effects Of Irradiation On Meat Qualitymentioning
confidence: 99%
“…The use of potassium lactate and sodium diacetate in frankfurter formulations in combination with pasteurizing doses of irradiation was influential in maintaining sensory attributes during both aerobic and vacuumpackaged storage (Knight et al, 2007a). There is an increasing effort to estimate microbial growth, taking into account the influence of intrinsic and extrinsic parameters of packaged cooked meat, using different predictive models (Devlieghere et al, 2000(Devlieghere et al, , 2001).…”
Section: Introductionmentioning
confidence: 99%